Evaluation of the golden proportion and golden standard of maxillary anterior teeth in relation to smile attractiveness - Swileh, Marwan Ahmed; Abuaffan, Amal Hussein; Alhajj, Mohammed Nasser (Brazilian Dental Science, 2019)
Objective: The present study aimed to explore the existence of golden proportion (GP) between the widths of maxillary anterior teeth and golden standard (GS) for width to height ratio of maxillary central incisor in individuals with attractive and non-attractive smiles. Material and Methods: A total 82 females were recruited and divided into 2 groups: attractive smile (n=41) and non-attractive smile (n=41). Frontal photographs were taken, scanned, and saved in a personal computer. The apparent mesiodistal width of each anterior tooth was measured. The data were analyzed using the appropriate statistical tests at a P-value of